2014
DOI: 10.1111/jnc.12813
|View full text |Cite
|
Sign up to set email alerts
|

Diet‐induced obesity accelerates the onset of terminal phenotypes in α‐synuclein transgenic mice

Abstract: Parkinson's disease (PD) and diabetes belong to the most common neurodegenerative and metabolic syndromes, respectively. Epidemiological links between these two frequent disorders are controversial. The neuropathological hallmarks of PD are protein aggregates composed of amyloid-like fibrillar and serine-129 phosphorylated (pS129) a-synuclein (AS). To study if diet-induced obesity could be an environmental risk factor for PD-related a-synucleinopathy, transgenic (TG) mice, expressing the human mutant A30P AS i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 55 publications
1
47
0
Order By: Relevance
“…Maintenance of the α-synuclein mutant mice on ADF reversed the autonomic deficit, whereas a high fat diet exacerbated the autonomic deficit (Griffioen et al, 2013). Consistent with the latter findings, a high fat diet hastened the onset of motor dysfunction and brainstem pathology in another line of α-synuclein mutant mice, which was associated with reduced activity of kinases known to be involved in neurotrophic factor signaling (Rotermund et al, 2014). In addition to enhancement of neurotrophic factor/BDNF signaling, IF may counteract PD-related pathogenic processes by stimulating autophagy.…”
Section: If and Health Indicators In Laboratory Animalsmentioning
confidence: 55%
“…Maintenance of the α-synuclein mutant mice on ADF reversed the autonomic deficit, whereas a high fat diet exacerbated the autonomic deficit (Griffioen et al, 2013). Consistent with the latter findings, a high fat diet hastened the onset of motor dysfunction and brainstem pathology in another line of α-synuclein mutant mice, which was associated with reduced activity of kinases known to be involved in neurotrophic factor signaling (Rotermund et al, 2014). In addition to enhancement of neurotrophic factor/BDNF signaling, IF may counteract PD-related pathogenic processes by stimulating autophagy.…”
Section: If and Health Indicators In Laboratory Animalsmentioning
confidence: 55%
“…Insulin resistance has been proposed to contribute to neurodegenerative diseases via a number of mechanisms, including promotion of disease-specific pathological lesions and an increase in neuronal vulnerability and neurodegeneration in general 194 . Many T2DM animal model studies have supported this concept that T2DM promotes the development and accumulation of ADRD pathologies, such as amyloid-β plaques, tau phosphorylation and neurofibrillary lesions 195 , and α-synuclein lesions 196 .…”
Section: Brain Insulin Resistancementioning
confidence: 95%
“…At the anatomical level, results from the cortical reconstruction of 527 individuals have revealed that excess adiposity is associated with cerebral white‐matter atrophy corresponding to a 10‐year older brain in people with obesity . Obesity may accelerate the onset of neurodegenerative phenotypes through the aggregation of α‐synuclein, pathological protein modifications, and neuroinflammation in mice . In humans, α‐synuclein also accumulates with age in brain; this accumulation not only accelerates the onset of Parkinson disease but also interacts with free fatty acid (FFA) in people with obesity and hyperlipidaemia .…”
Section: Obesity Drives Ageing At Multiple Levelsmentioning
confidence: 99%